Элементарный побег и сезонное развитие растений Silene jailensis (Caryophyllaceae) — реликтового эндемика Горного Крыма - Никифоров, А.Р. (Український ботанічний журнал, 2011)
Вивчалися особливості циклу розвитку елементарного пагона Silene jailensis залежно від термічних умов сезонного періоду. Цикл елементарного пагона рослин ex situ в Південному Криму припадає на період з весни до осені. Цикл розвитку елементарного пагона рослин in situ охоплює два сезони: початковий етап улітку та восени попереднього року, коли створюється зона відновлення пагона, а завершальний — навесні наступного року, коли формується зона збагачення з вегетативно-генеративними бруньками. Подібний цикл мають деякі пагони і в рослин ex situ. У цьому разі основний вегетативний приріст формується восени, а завершальна вегетативно-генеративна частина пагона — після зимової паузи. Виявлений потенціал у розвитку елементарного пагона свідчить, що його цикл у рослин in situ є формою їхньої адаптації до екологічно межових умов розвитку у прохолодному кліматі. Peculiarities of the elementary shoot development of Silene jailensis depending on thermal conditions were studied. The development cycle of elementary shoots of the plants ex situ in Southern Crimea lasts from spring to autumn. In situ the elementary shoots grow during two seasons: the first stage takes place in summer and autumn of the previous year when a zone of shoot renewal is formed, and the final stage continues from spring of the following year when the zone of enrichment with vegetative and generative buds is developed. Some shoots of the plants ex situ have the same cycle. In this case the main vegetative parts of the shoot grow in autumn, and the final vegetative-generative parts develop during the spring rise of average day temperatures after the winter pause. The revealed potential in the development of elementary shoots in situ shows their adaptability to extreme ecological conditions in cool climate.